1999
DOI: 10.1103/physrevb.59.r14169
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic scaling in the underdoped superconductorHg0.8Re0.2Ba2

Abstract: An approach has been made to deduce the second moment contribution of the planar Cu NMR line from indirect nuclear couplings, using the middle plane sites of the trilayer superconductor, Hg 0.8 Re 0.2 Ba 2 Ca 2 Cu 3 O 8 (T c ϭ126 K). We find that T 1 fluctuations of neighboring nuclear spins in the plane are the dominant causes of the spin-echo decay observed in the present case of an external field perpendicular to the c axis. Taking account of this effect in the analysis, the second moment is deduced. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Each curve was obtained by adding the real part of the FT spectra of the half echo measured at a few different frequencies [12]. The relatively narrow and wide lines are assigned to Cu(1) and Cu(2) sites in the inner and outer layers, respectively [13]. We confirmed that K s and the quadrupole frequency (ν Q ) are consistent with previous results [14,15].…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Each curve was obtained by adding the real part of the FT spectra of the half echo measured at a few different frequencies [12]. The relatively narrow and wide lines are assigned to Cu(1) and Cu(2) sites in the inner and outer layers, respectively [13]. We confirmed that K s and the quadrupole frequency (ν Q ) are consistent with previous results [14,15].…”
supporting
confidence: 89%
“…(11). Provided again that the q-dependences of χ ij (q) around Q are weaker than that of F q , T −2 2M at 0 • and 90 • can be rewritten as [6,13],…”
Section: Mmentioning
confidence: 99%
“…According to the SCR theory [23] or the renormalization group study [24], ξ 2 AF ∝ (T + c) −1 in two-dimensional systems, which is observed in high-T c cuprates around the optimum doping [25]. This relation is also reproduced well by the FLEX approximation [15].…”
mentioning
confidence: 72%
“…The hole concentration p is estimated from[8]. A triangle[4], a cross[6], a square[5], and closed circles (the present works) indicate pseudogap temperatures T * 's. Open circles are T c 's.…”
mentioning
confidence: 82%
“…The spin pseudogap opens below T * . The Cu nuclear spin-lattice relaxation studies revealed the pseudogap for underdoped single crystals with T c = 115 K (T * = 230 K) [4], an underdoped Re-substituted powder sample with T c = 126 K (T * = 172 K) [5], and an optimally doped powder sample with T c = 133 K (T * = 160 K) [6,7]. Closed circles and crosses are for as-synthesized and O 2 -annealed samples, respectively.…”
Section: Introductionmentioning
confidence: 99%